(untitled) (Research, Society and Development, 2021)
Watermelon is mainly recognized for its high antioxidant capacity natural in its pulp and peel, although the latter is mostly discarded, it has relevant nutrients. The objective of this work was to study the use of crushed watermelon rind to obtain extracts with antioxidant activity through the use of extraction techniques such as the Soxhlet system, maceration and ultrasound-assisted extraction, using organic solvents of different polarities. The extracts were evaluated by the yield of the extraction process, where, in all analyses, the solvent with the best performance was ethanol. For the total phenolic content (TFT), the extraction technique by maceration with 3487.75 mg/g was highlighted, in the determination of the antioxidant activity (AA), using the ABTS and DPPH radicals. The antioxidant potential by the maceration extraction method was 45,16% and in Soxhlet it was 40,7% inhibition. Thus, it can be concluded that watermelon rind is a raw material with significant antioxidant potential.